Mini Basketball Game against Early Childhood Gross Motoric Skills - Syamsuarni K Syamsuarni K; Arismunandar Arismunandar; Rusmayadi Rusmayadi; Herlina Herlina; Wahira Wahira (International Journal of Multidisciplinary Approach Research and Science, 2026)
Play has a huge influence on the development of a child. Children do not care whether their physical and psychological condition is good or not; everything is done with pleasure, because, in essence, play is a necessity for children. Therefore, the role of parents and teachers is needed in providing direction and supervision. Parents and teachers also play a role in choosing games that align with the children's developmental level, not just for the children's liking. This study aims to: (1) find out the description of gross motor skills in early childhood, (2) describe the gross motor skills of early childhood, (3) analyze the influence of mini basketball games on the improvement of gross motor skills in early childhood. This study uses an experimental method; the data collection techniques are observation and documentation. Data analysis is conducted to test the proposed hypothesis, namely, the influence of mini basketball games on children's gross motor skills. The results of the study showed that mini basketball games have a positive and significant influence on improving gross motor skills of children aged 5–6 years. Mini basketball games have proven to be a fun and educational way to develop the motor skills of young children and those in early childhood. The play-based approach in physical learning has been proven effective in stimulating children's overall development. The results of this study can serve as a reference for designing learning activities that focus on developing gross motor skills through active games such as mini basketball.